RESEARCH ON GENERATING INTELLIGENT TEACHING RESOURCESFOR CHINESE GRAMMAR BASED ON LARGE LANGUAGE MODEL AGENTS (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
Digital and intelligent technologies open new avenues for developing international Chinese language teaching resources. This paper focuses on leveraging large language models to empower the development of intelligent teaching resources for Chinese grammar, closely aligning with practical teaching needs. It explores the conceptual orientation and practical pathways for constructing intelligent teaching resources. The development of intelligent teaching resources is guided by three principles: overall design adheres to standardization and systematization; content design prioritizes learner-centered dynamic adaptation; and technological application emphasizes multimodal integration and iterative data updates. Taking Level 3 grammar points-commonly taught in the Chinese Proficiency Standards for International Chinese Education-as a breakthrough point, this paper addresses practical needs in Chinese grammar instruction. It generates sample intelligent teaching resources for Level 3 grammar points using a Chinese grammar AI agent, focusing on five resource types: grammar exercise banks, contextual training resources, intelligent grammar diagnostics, teacher support materials, and grammar knowledge mind maps. The analysis of its generation process and outcomes aims to contribute to the development of digital and intelligent teaching resources for international Chinese language education.